MHD natural convection flow of casson ferrofluid at lower stagnation point on a horizontal circular cylinder - Muhammad Khairul Anuar, Mohamed; Ong, Huei Ruey; Siti Khuzaimah, Soid; Alkasasbeh, Hamzeh Taha (Semarak Ilmu Publishing, 2024)
This study extends the mathematical model of MHD free convection flow on horizontal circular cylinder, with considering theCasson ferrofluid, specific to a stagnation region case. The set of non-linear partial differential equations that governed the model is first transformed to a simpler set of equations using the non-similar transformation. This set of equations then reduced to ordinary partial equations which reflects to the case of stagnation region and solved numerically using the implicit finite difference method known as the Keller-box method. Blood and magnetite are taken as the based-fluid and the ferroparticles for the Casson ferrofluid, respectively. From the numerical study, it was found that the Casson ferrofluid with the same Prandtl values had higher thermal and velocity boundary layer thicknesses compared to a Newtonian ferrofluid. The increase of Casson parameter reduced the thermal boundary layer thickness which physically enhanced the Nusselt number.